Strategies for Channelizing Women Artisans as Entrepreneurs and Marketing of Handicraft Products : An Empirical Study - Yadav, Uma Shankar; Tripathi, Ravindra; Tripathi, Mano Ashish; Kumar, Parmod (Indian Journal of Marketing, 2023)
Purpose : The study aimed to identify women’s entrepreneurship in the handicraft sector, suggest marketing strategies, and develop strategies for sustainable development and capacity building of women in this sector. When the world suffered during the COVID-19 pandemic, Indian migrant workers in other countries returned to their home countries because of job loss or cost-cutting by industry owners. In that situation, women in the handmade industry emerged as new entrepreneurs. Research Design/Methodology : We used the descriptive research method for this study. The data were examined using a stratified random sampling technique and related tools and software, notably SPSS. The correlation and ANOVA statistical procedures were used to test the hypotheses. Findings : Based on the data analysis and discussion, we discovered that strong methods for promoting the handicraft industry and women’s entrepreneurship could be devised to address the entrepreneurial dilemma. During a pandemic, this industry should have its own set of supported packages. Implications of the Research : Managers, legislators, and societal progress all profited from this. The handicraft industry was established to provide jobs for women living in rural and semi-urban areas. Our research was conducted using a trim-level sample size; therefore, it was unconstrained. By promoting fairness, marketing equilibrium, and diverging marketing economies for inclusive development, the growth of the handicraft industry improved sustainability. Originality : This study focused on women-led handicraft businesses in Indian and global marketplaces. This study was the first to include new and robust strategies.